Immunoglobulin prophylaxis prevents hospital admissions for fever in pediatric acute lymphoblastic leukemia: results of a multicenter randomized trial - Thus, Kirsten A.; Groot-Kruseman, Hester A. de; Winkler-Seinstra, Pauline; Fiocco, Marta; Segers, Heidi; Bos, Cor van den; Sluis, Inge M. van der; Tissing, Wim J. E.; Veening, Margreet A.; Zwaan, Christian Michel; Tilburg, Cornelis M. van; Pieters, Rob; et al. (Haematologica, 2025)
Infections lead to substantial morbidity during the treatment of acute lymphoblastic leukemia (ALL) in which the adaptive immune system is severely affected, leading to declining serum immunoglobulin levels. We performed a trial to investigate whether intravenous immunoglobulin (IVIG) prophylaxis in pediatric patients with ALL could prevent admissions for fever. This randomized controlled trial was a subtrial of the national Dutch multicenter ALL study. Patients aged 1-19 years with medium-risk ALL were randomized into two groups receiving either IVIG prophylaxis (0.7 g/kg IVIG given every 3 weeks, starting on day 22 after diagnosis) or well-defined standard of care (control group). Between October 2012 and March 2019, 91 (51%) patients were randomly assigned to IVIG prophylaxis and 86 (49%) to the control arm. In the IVIG prophylaxis group there were 206 admissions for fever versus 271 in the control group (P=0.011). IVIG prophylaxis was not associated with bacteremia. However, there were significantly fewer admissions for fever with negative blood cultures in the IVIG prophylaxis group than in the control group (113 vs. 200, P<0.001). The difference in number of admissions for fever was observed specifically during maintenance treatment (100 vs. 166, P<0.001) resulting in fewer courses of antibiotic treatment (78 vs. 137, P<0.001) and fewer cases of chemotherapy adaptation (72 vs. 134, P<0.001). In conclusion, in pediatric patients with medium-risk ALL, IVIG prophylaxis was associated with significantly fewer admissions for fever with negative blood cultures during maintenance treatment, resulting in fewer courses of antibiotic treatment and fewer chemotherapy adaptations.